PENERAPAN MODEL PEMBELAJARAN LANGSUNG (DIRECT INSTRUCTION) UNTUK MENINGKATKAN KEMANDIRIAN DAN PRESTASI BELAJAR PESERTA DIDIK - Herwanto Herwanto (DIADIK, 2022)
This study aims to describe the application of direct learning models and describe the effectiveness of direct learning models to increase  the self-reliance and learning achievement of learners in the XII class of science at SMA Negeri 1 Kota Agung. The design of the research used was Class Action Research (PTK) and experimental research. The subject in this study is an XII class science at SMA Negeri 1 Kota Agung during semester 2 of the 2020/2021 school year. As for number of students for the PTK class was 25 people, for the experimental class there were 25 people, and for the control class there were 26 people. The method of collecting data in this study uses the teacher activity, observation sheet application of a direct learning model (direct instruction), a self- reliance observation sheet learning and student learning result. The data analysis uses an average score and tests made up of different tests between cycles and two separate samples that are unrelated. Research shows that application of direct learning models can enhance efficiency, learn and effectively improve students learning on XII science class economics at SMA Negeri 1 Kota Agung